2021
DOI: 10.1002/adfm.202108047
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent and Conductive Indium‐Free Vanadates Crystallized at Reduced Temperature on Glass Using a 2D Transparent Nanosheet Seed Layer

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
(125 reference statements)
2
7
2
Order By: Relevance
“…We noted that the FOM values of SVO films grown on CNO nanosheets were lower than those of SVO films grown on single crystals by MBE. That is not consistent with the reported data in reference [ 27 ] even though SVO films in this study had lower resistivity than the reported data [ 27 ] and similar transmittance values (see SrVO 3 note in SI). Furthermore, Figure 3e shows FOM values of SMO and SNO in comparison with other films reported in the literature in the UV spectrum of 3.85–4.5 eV.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…We noted that the FOM values of SVO films grown on CNO nanosheets were lower than those of SVO films grown on single crystals by MBE. That is not consistent with the reported data in reference [ 27 ] even though SVO films in this study had lower resistivity than the reported data [ 27 ] and similar transmittance values (see SrVO 3 note in SI). Furthermore, Figure 3e shows FOM values of SMO and SNO in comparison with other films reported in the literature in the UV spectrum of 3.85–4.5 eV.…”
Section: Resultscontrasting
confidence: 89%
“…showed that correlated CaVO 3 and SrVO 3 (SVO) films with a thickness of 40 nm on Ca 2 Nb 3 O 10 (CNO) nanosheets on glass had the RT optical resistivity values of 260 and 274 µΩ cm, respectively, and the high optical transmittance of about 75% at 550 nm (2.25 eV). [ 27 ] We also observed similar resistivity values of SVO on CNO nanosheets [ 27 ] due to the low growth temperature and/or the influence of the substrate materials (see SrVO 3 note in Supporting Information). Furthermore, it was revealed that 4d correlated metals SrMoO 3 (SMO) and SrNbO 3 (SNO) have higher UV‐vis transmittance compared to 3d SVO due to interband transitions occurring at higher photon energies of 4.3–4.8 eV, [ 9,14,17,19 ] while these three correlated metals on single crystal substrates were reported to have similar resistivity values of around 30 µΩ cm.…”
Section: Introductionsupporting
confidence: 61%
“…For both kinds of films, epitaxial and polycrystalline, the transmittance decreases with the wavelength between 480 and 400 nm due to a characteristic interband transition of SVO from the low-lying O bands to the V valence band. 3 On the other hand, films heated to 250 °C no longer show this decrease in transmittance which can be explained by the loss of For the epitaxial films (Figure 7a), η T show a maximum for the aging temperature of 200 °C, related to its excellent transmission of about 90% at 500 nm. For the polycrystalline films (Figure 7d), η T slightly decreases with aging up to 200 °C and abruptly increases for an aging at 250 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Interestingly, the as-deposited sample still shows a metallic temperature dependence, indicating that the grain boundaries do not perturb strongly the electrical conduction, as was also observed in optical measurements. 3 The influence of the grain boundaries on the electrical transport seems to be also limited, as the charge density is observed to be 1.7 × 10 22 cm −3 . This value, very close to the theoretical value, may indicate a lesser influence of oxygen vacancies than in the epitaxial films, but the chemically and structurally perturbed grain boundary regions are probably trapping some charges.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The crystallization of complex oxides from amorphous precursor layers is a promising route toward the creation of epitaxial materials and three-dimensional heterostructures with an expanded range of compositions and geometries . Seeding methods based on nanocrystals or transferred membranes initiate nucleation and remove the need for a single-crystal substrate. Seeded solid-phase epitaxy (SPE) expands the possibility of developing functional epitaxial layers for geometries and materials for which templating substrates are not available, such as single-crystal growth over large areas on amorphous substrates or on crystalline substrates with lattice symmetry that is different from the crystallizing material. The crystal structure and orientation of the seed crystal provides a template for lateral crystallization. , Complex strain states can evolve as a result of the thin-film stress associated with the density changes across the crystal–amorphous interface.…”
mentioning
confidence: 99%